Asia Bond Monitor. ([Manila] Asian Development Bank, 2019)
This issue of the Asia Bond Monitor discusses the impact of US monetary policy uncertainty on emerging market currency rates as well as the growing importance of domestic capital markets. It also looks at the progress of global efforts to transition away from the use of the London Interbank Offered Rate, the widely used benchmark rate in global financial markets.
Keywords: Finance; Financial institution; Electronic books